Characterization of Quezon City aquifer system using archydro groundwater module and risk assessment using susceptibility index method - Bronzi, Martha Elizabeth P.
The Susceptibility Index Method was used to evaluate the vulnerability of the groundwater system of Quezon City. This method considered the factors depth to water table, net recharge, aquifer media, topography, and land use in the analysis. The study determined the level of vulnerability of Quezon City's groundwater system and its aquifer characteristics. The study will aid in the analysis of the sustainability of the groundwater resources in Quezon City. This will also help in the protection of pollution prone areas. It is concluded that the aquifer system has moderate to high vulnerability. The aquifer system has the following characteristics: mostly discontinuous urban areas, a relatively deep water table, a high net recharge, an average percent rise, and aquifer media composed of mostly sandstone/limestone/shale sequences, adobe, and sand and gravel.